PENGARUH PENGEMBANGAN KARIR, PERSEPSI TENTANG KEADILAN ORGANISASI, DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fory Armin Naway (Jurnal Manajemen., 2014)
The objective of this research is to study the effects of career development, perception of organizational justice and job satisfaction on teacher’s organizational citizenship behavior of The Public Senior High School in Gorontalo Regency, Gorontalo Province. This research used the quantitative approach with the survey method. The samples of this research were 178 employees selected randomly. The data were obtained by distributing questionnaires and analyzed by using the descriptive statistics and path analysis in inferential statistics. The results of the research can be concluded that: career development had a direct effect on teacher’s organizational citizenship behavior, perception of organizational justice had a direct effect on teacher’s organizational citizenship behavior, job satisfaction had a direct effect on teacher’s organizational citizenship behavior, career development had a direct effect on teacher’s job satisfaction, perception of organizational justice had a direct effect on teacher’s job satisfaction. Therefore to improve teacher’s organizational citizenship behavior, career development, perception of organizational justice, and job satisfaction should be improved.